Group dynamics for teams - Levi, Daniel (Thousand Oaks SAGE, 2014)
Group Dynamics for Teams, Fourth Edition, by Daniel Levi, explains the basic psychological concepts of group dynamics with a focus on their application with teams in the workplace. Grounded in psychology research but with a very practical focus on organizational behavior issues, this fully updated Fourth Edition helps readers understand and participate in teams more effectively in their day-to-day work.
Includes bibliographical references and index.
Keywords: Teams in the workplace